The Role of Women Headed Households in the Local Seed Business in Ethiopia: The Case of Jabi Tehnan, Bure and Yilmana Densa Districts (Global Journal of Human-Social Science, 2018)
This study was conducted to assess the role of women headed households in the Local Seed Businesses and to analyze the determinant factors that influence women headed households benefit in the local seed business The research method of this study was quantitative research method and descriptive research design was employed as a research design Women in the local seed business were most frequently participated in seed production activities such as weeding harvesting and storage of seeds chemical fertilizer application and sowing of seeds On the other hand their participation in leadership applying pesticides trainings organic fertilizer use and active participation in meetings were limited The Binary Logistic Regression analysis indicated different variables that determine women headed households benefit status in seed producer cooperatives that factors such as land plot size land used for local seed business soil fertility oxen ownership access to market access to credit services and access to extension services had significant effects on benefits gained by women headed households from the local seed business To enhance the involvement of women headed households in the local seed business and to enable them benefit from their efforts it seems imperative that government and non government institutions should develop a solid package on seed production and carry out capacity buildings that could empower women
Keywords: morality; ethics; poverty; sustainable solution; bangladesh